2009
DOI: 10.1007/s00421-009-1240-1
|View full text |Cite
|
Sign up to set email alerts
|

Can HRV be used to evaluate training load in constant load exercises?

Abstract: The overload principle of training states that training load (TL) must be sufficient to threaten the homeostasis of cells, tissues, organs, and/or body. However, there is no "golden standard" for TL measurement. The aim of this study was to examine if any post-exercise heart rate variability (HRV) indices could be used to evaluate TL in exercises with different intensities and durations. Thirteen endurance-trained males (35 +/- 5 year) performed MODE (moderate intensity, 3 km at 60% of the maximal velocity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0
11

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 28 publications
6
73
0
11
Order By: Relevance
“…Previous research has proposed that the time course of vagal recovery depends primarily on exercise intensity (Arai et al, 1989;Stejskal et al, 2001), and/or cardiorespiratory performance (Hautala et al, 2001;Seiler, Haugen, & Kuffel, 2007). However, exercise duration should also be considered as a factor that influences ANS recovery (Kaikkonen, Hynynen, Mann, Rusko, & Nummela, 2010). A number of studies have focused on ANS recovery in response to distance running e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has proposed that the time course of vagal recovery depends primarily on exercise intensity (Arai et al, 1989;Stejskal et al, 2001), and/or cardiorespiratory performance (Hautala et al, 2001;Seiler, Haugen, & Kuffel, 2007). However, exercise duration should also be considered as a factor that influences ANS recovery (Kaikkonen, Hynynen, Mann, Rusko, & Nummela, 2010). A number of studies have focused on ANS recovery in response to distance running e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as sub-elite referees have less time for training than their elite counterparts, HRV monitoring could be an interesting approach for time economy in training individualisation. HRV has been extensively utilised as a non-invasive tool for the assessment of cardiac autonomic nervous system modulation (Task Force of the European Society of Cardiology and the North American Society of Pacing and Electrophysiology 1996) in the trained state (Leicht et al 2003a;Hautala et al 2009), during the short-term (Kaikkonen et al 2010) and long-term (Hautala et al 2001) post-exercise recovery; and following psychological stressors (Hamer and Steptoe 2007). Given the high physical Mallo et al 2009) and psychological (Boyko et al 2007;Weston et al 2006) demands of soccer refereeing, it is important to assess the impact of soccer matches on cardiac autonomic control (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,39−41 Conversely, exercise duration seems not to affect so much HR recovery dynamics; 5,9 just by increasing total time 4-fold or more we do find a significant change in parasympathetic reactivation. 4 When talking about supra maximal interval protocols, Buchheit et al 1 showed a significant slower parasympathetic reactivation after a Repeated Sprint exercise compared with a continuous one of equivalent net caloric expenditure, concluding that anaerobic metabolism participation rather than energy expenditure modulates the level of post exercise parasympathetic reactivation. A similar depressed post exercise cardiac autonomic response has been reported by other authors using Wingate test 8,10,12,19 and Repeated Shuttle Sprint.…”
Section: Discussionmentioning
confidence: 99%
“…As in recent studies, the frequency limit of 1.0 Hz was chosen to include the respiratory frequency to the analysis. 4,5,7 LF/HF ratio was also retained for statistical analysis.…”
Section: −35mentioning
confidence: 99%